Control of innate immunity and lipid biosynthesis in neurodegeneration - Scoles, Daniel R.; Pulst, Stefan M. (Frontiers in Molecular Neuroscience, 2024)
The cGAS-STING innate immunity pathway and the SREBP-activated cholesterol and fatty acid synthesis pathway are abnormally co-regulated in neurodegenerative disease. Activation of STING signaling occurs at the endoplasmic reticulum (ER) membrane with STING anchored by INSIG1 along with SREBP and the sterol-bound SREBP cleavage activating protein (SCAP) when sterols are in abundance. When sterols are low, the INSIG-dependent STING pathway is inactivated and the SREBP-SCAP complex is translocated to the Golgi where SREBP is cleaved and translocated to the nucleus to transactivate genes for cholesterol and fatty acid synthesis. Thus, there is inverse activation of STING vs. SREBP: when innate immunity is active, pathways for cholesterol and fatty acid synthesis are suppressed, and vice versa. The STING pathway is stimulated by foreign viral cytoplasmic nucleic acids interacting with the cyclic GMP–AMP synthase (cGAS) DNA sensor or RIG-I and MDA5 dsRNA sensors, but with neurodegeneration innate immunity is also activated by self-DNAs and double-stranded RNAs that accumulate with neuronal death. Downstream, activated STING recruits TBK1 and stimulates the transactivation of interferon stimulated genes and the autophagy pathway, which are both protective. However, chronic activation of innate immunity contributes to microglia activation, neuroinflammation and autophagy failure leading to neurodegeneration. STING is also a proton channel that when activated stimulates proton exit from STING vesicles leading to cell death. Here we review the salient features of the innate immunity and cholesterol and fatty acid synthesis pathways, observations of abnormal STING and SREBP signaling in neurodegenerative disease, and relevant therapeutic approaches.